The Correlations between Language Learning Strategies and English Achievement of the Undergraduate Students of English Education Study Programs - Nurul Fitriyah Almunawaroh (Jurnal Bahasa dan Sastra, 2019)
Abstract: Language learning strategies (LLS) is one of important factors in learning process. The aim of this study is to investigate the correlation between students’ LLS and students’ English achievement (EA) and to find the influence of students’ LLS to students’ EA. Strategy Inventory for Language Learning (SILL) was administered to 103 student at Sriwijaya, Muhammadiyah, and Tamansiswa universities. Students’ EA was gained from their grade point average (GPA). Metacognitive strategy, affective strategy and EA had negative significant correlations. Furthermore, compensation strategy positively and significantly correlated with EA of the students in Sriwijaya-Muhammadiyah Universities. Meanwhile, affective strategy and EA of the students in Sriwijaya-Muhammadiyah, Sriwijaya, and Taman Siswa Universities were negatively and significantly correlated. Additionaly, metacognitive, affective and EA of the students in Sriwijaya-Muhammadiyah Universities negatively and significantly correlated. The influence of each of the six on EA was 8.6%, 9.4%, 35.3%, 15.1%, 13%, 3.5% for affective, and 7.8% for compensation.Keywords: Language learning strategies, English achievement, undergraduate studentsAbstrak: Strategi Pembelajaran Bahasa (SPB) merupakan salah satu faktor penting dalam proses pembelajaran. Tujuan dari penelitian ini adalah untuk menyelediki hubungan korelasi antara SPB mahasiswa dan prestasi Bahasa Inggris (PBI), dan untuk mengetahui pengaruh SPB mahasiswa terhadap PBI mahasiswa. Angket Strategy Inventory for Language Learning (SILL) didistribusikan ke 103 mahasiswa di Universitas Sriwijaya, Muhammadiyah, dan Tamansiswa. PBI mahasiswa diperoleh dari indeks prestasi kumulatif (IPK). Startegi metakognitif, afektif, dan PBI memiliki korelasi negatif dan signifikan. Selanjutnya, strategi kompensasi berkorelasi positif dan signifikan dengan PBI mahasiswa di Universitas Sriwijaya-Muhammadiyah. Sementara itu, strategi afektif dan PBI mahasiswa di Universitas Sriwijaya-Muhammadiyah, Sriwijaya, dan Taman Siswa berkorelasi negatif dan signifikan. Selain itu, metakognitif, afektif dan PBI mahasiswa di Universitas Sriwijaya-Muhammadiyah berkorelasi negatif dan signifikan. Pengaruh masing-masing dari keenam strategi terhadap PBI mahasiswa adalah 8,6%, 9,4%, 35,3%, 15,1%, 13%, 3,5% untuk afektif, dan 7,8% untuk kompensasi.Kata-kata kunci: Strategi pembelajaran bahasa, prestasi bahasa Inggris, mahasiswa sarjana.